Art Education as Social Experience: Victor D’Amico and the Origins of MoMA’s Progressive Educational Project - Elena Sidorova (Transatlantica)
The paper addresses the issue of education in art museums. It examines the first attempt to establish an art education project at the Museum of Modern Art (MoMA) in New York. Firstly, the paper explains why MoMA based its original art education program on the fundamental ideas of John Dewey’s theories of progressive education. Secondly, it analyzes the grassroots of five progressive art education initiatives launched by MoMA’s founding Director of the Department of Education Victor D’Amico in 1937-1969. The paper concludes that D’Amico’s experiential philosophy of art education, although no longer practiced at MoMA, advanced the value of art education as social experience in art pedagogy both in the United States and abroad.